The investigation of relaxation processes in chosen liquid crystals by ultrasonic and dielectric methods - DRZYMAŁA, Adam (Archives of Acoustics, 1981)
Relaxation processes have been found to occur in 4-n-methoxybenzoated-4-n-pentylphenylene and 4-n-octyloxyphenylene-4-m-pentyloxybenzoate. The findings are based on ultrasonic and dielectric investigations. Both chemical compounds exhibit two regions of relaxation in the range of frequencies investigated. A comparison has Men made of the values of the activation energy derived from the dielectric and acoustic investigations.